2021
DOI: 10.3390/ma15010144
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Behavior and Susceptibility to Stress Corrosion Cracking of Leaded and Lead-Free Brasses in Simulated Drinking Water

Abstract: Duplex α + β’ brasses are widely used in drinking water distribution systems for tube fittings, valves, and ancillaries because they are low cost, easy to fabricate, and exhibit high mechanical strength. However, depending on application conditions and alloy composition, they may undergo dealloying and stress corrosion cracking. In this research, three different brass types, two leaded (CW617N and CW602N) alloys and one lead-free brass (CW724R), were investigated to assess their corrosion behavior and suscepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Furthermore, protective coatings can be employed to further enhance the corrosion resistance of the material. As the Zn content range where this effect occurs is extensive, there are limited alloy design strategies that can be employed as of yet to alleviate SCC in brasses [86,87,95,96]. The fracture caused by SCC usually follows an intergranular path with multiple branching patterns.…”
Section: Stress Corrosion Cracking (Scc)mentioning
confidence: 99%
“…Furthermore, protective coatings can be employed to further enhance the corrosion resistance of the material. As the Zn content range where this effect occurs is extensive, there are limited alloy design strategies that can be employed as of yet to alleviate SCC in brasses [86,87,95,96]. The fracture caused by SCC usually follows an intergranular path with multiple branching patterns.…”
Section: Stress Corrosion Cracking (Scc)mentioning
confidence: 99%
“…Due to the unique combination of non-magnetism, good machinability, superior corrosion resistance [1], relative strength, higher thermal conductivity [2], electrical conductivity, formability [3], and low cost, brasses are widely used in drinking water distribution systems [4,5], heat-transfer units [2], and other industries for water filtration [6], elbow fitting [7], nuts [8], etc. Brasses are copper-zinc alloys with the Zn content between 5% and 40% [9].…”
Section: Introductionmentioning
confidence: 99%
“…The dezincification behavior of low-Pb duplex brasses has been systematically studied by Michael et al Results showed that in addition to less β' phase fraction, a small α grain size with high aspect ratio can also improve the dezincification resistance [12]. Silicon brasses were investigated to increase strength or produce environment-friendly alloys with excellent dezincification resistance [4,13]. CuZn21Si3P forms a complex triple-phase, containing about 60% of α phase with some Si-rich κ (Cu8Zn2Si) phase and γ (Cu4ZnSi) phase.…”
Section: Introductionmentioning
confidence: 99%